Is highly purified cannabidiol a treatment opportunity for drug‐resistant epilepsy in subjects with typical Rett syndrome and CDKL5 deficiency disorder? - Aglaia Vignoli; Giulia Prato; Enrico Alfei; Irene Bagnasco; Alberto Danieli; Massimiliano Celario; Jacopo Favaro; Sara Matricardi; Francesca Felicia Operto; Alessandro Orsini; Davide Paolo Bernasconi; Nicola Pietrafusa; et al. (Epilepsia Open)
Abstract Objective This study aimed to evaluate the efficacy and safety of adjunctive, highly purified Cannabidiol (Epidiolex®) in individuals with drug‐resistant epilepsy (DRE) due to genetically determined typical Rett Syndrome (RTT) and CDKL5 Deficiency Disorder (CDD). Methods We recruited subjects with genetically confirmed typical RTT and CDD with drug‐resistant seizures who received add‐on treatment with highly purified Cannabidiol (CBD) through a national collaboration group. CBD treatment was titrated from 5 to 20 mg/kg/day; concurrent antiseizure medications (ASMs) could have been adjusted as clinically indicated. Results We enrolled 27 subjects (26 females), carrying a MECP2 genetic variant (14 subjects, 51.9%) or a CDKL5 genetic variant (13 subjects, 48.1%). Median age [IRQ] of individuals was 10.5 [7.9, 18.5] years. The median dose of CBD [IRQ] at last follow‐up was 15 [11.12, 18.8] mg/kg/day, in association with a mean of 3 ASMs (range 2–4). The median duration of treatment was 14 [8.5, 20] months. Although not reaching a significant statistical effect, CBD reduced the incidence of seizures with respect to the baseline in 18/27 (66.6%) subjects, with 7 (25.9%) showing a seizure reduction >75%, and 11 (40.7%) >50%. The most relevant adverse events were somnolence seen in 3 subjects, irritability/agitation in 2 subjects, loss of appetite in 2 subjects, and insomnia in 1 individual. Caregivers reported an improvement in attention and reactivity in 12 subjects (44.4%), in sleep quality in 5 subjects (18.5%), and in motor aspects in 3 patients (11.1%). Significance CBD resulted effective in reducing seizure frequency in 66.6% of the study sample, regardless of the pathogenic variant; side effects were mild, and caregivers reported an improvement in behavioral and motor features. Plain Language Summary This study explored the use of highly purified Cannabidiol (CBD, Epidiolex®) as an add‐on therapy for individuals with drug‐resistant epilepsy due to Rett Syndrome (RTT) or CDKL5 Deficiency Disorder (CDD). Twenty‐seven participants received CBD alongside their usual ASMs. After a median treatment duration of 14 months, 66.6% experienced fewer seizures, with some showing over 75% reduction. Side effects were generally mild, mainly sleepiness or irritability. Notably, caregivers reported improvements in attention, responsiveness, sleep, and motor function. While results were not statistically significant, they suggest CBD may benefit seizure control and quality of life in RTT and CDD patients.